The Comparation Study of Pasteurized "Fruits Up" Products Using TPC (Total Plate Count) Method - Bunyamin Anas; Siahaan Putri Natasha; Purnomo Dwi; Nawawi Marlis (Agroindustrial Journal, 2020)
Fruits Up is one of the small and medium sized enterprises (SMEs) which is engaged in developing puree mango beverage. To satisfy the consumer, Fruits Up decided not to use chemical preservatives as a solution to be a healthy drink with longer shelf life time product. The purpose of this research is to conduct pasteurization process on Fruits Up product as solution of increasing product shelf life time without the use of chemical preservatives. Comparison of existing products will be analyzed using microbiological quantitative analysis with Total Plate Count (TPC) method and presented in the form of Standard Plate Count (SPC). The sampling method was using a Completely Randomized Factorial Design with difference room temperature and storage time (1 day, 3 day and 5 day). According to the result, the least amount of bacteriology is present in the pasteurized Fruits Up product with H1 storage of refrigerator temperature (10°C) and the highest amount is found on Fruits Up products that have not been pasteurized with H5 storage of room temperature (26°C). Based on the results, a significant decrease in TPC occurs during the pasteurization process so that the pasteurization process is highly recommended to be performed permanently